The influence of Green Creativity and Green transformational leadership on Environmental Performance - Mentari Clara Dewanti; Daisy Marthina Rosyanti; Fani Khoirotunnisa (Future Science, 2023)
The development of more ecologically friendly goods, methods, and technologies is encouraged by green creativity. Inadequate use of natural resources, greenhouse gas emissions, and air and water pollution can all be reduced as a result. The goal of the leadership strategy known as